Zdrowie w systemie wartości menedżerów = Health in the value system of managers - Šingaev, Sergei M. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article analyzes the system of values of modern Russian Manager and the place of health in this system. Identified four basic, from the point of view of managers, value: "Health (physical and mental)", "Interesting work", "Love (spiritual and physical intimacy with a loved one)", "Happy family life". At least find in the profession the transformation of values: health comes to the fore, there is an awareness of the importance of health as a universal value.
Keywords: zdrowie; system wartości; menedżerowie; profesjonalne zdrowie; health; values; manager; professional health